(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This survey was conducted from June 2004 to May 2005 to study the current status of ticks infesting cattle in South Darfur State, Sudan. Tick collection was carried out at two months intervals from sedentary and semi sedentary cattle of three age groups namely calves less than 2 years old, 2 to 4 years old heifers or steers and more than 4 years old adults. The collection covered five localities, Nyala, Edd-alferrsan, Tulus, Reheid-albirdi and Umdafug where tick control measures were not practiced. Four genera and 15 species of ticks were identified. These included Amblyomma lepidum, A. variegatum, Hyalomma anatolicum, H. dromedarii, H. impeltatum, H. rufipes, H. impressum, H. truncatum, Boophilus annulatus, B. decoloratus, Rhipicephalus evertsi evertsi, R. guilhoni, R. muhsamae, R. praetextatus and R. sanguineus sanguineus. The highest tick load was during the rainy season. Cows carried more ticks than oxen while calves carried lower numbers. Cattle with white coat colour were infested by higher numbers of ticks compared to animals with brown or black coat colour. The survey revealed that H. anatolicum and A. lepidum has spread and established in western parts of the country. It will not be surprising for these economically important tick species to spread and establish in the West African countries and hence new tick borne diseases to emerge